Anterior–posterior and medial-lateral balance metrics are unchanged when two-dimensional pseudorandom motion perturbations are provided in semicircular canal coordinates - Fujii, Manami; Chirumbole, Sophia G.; Wagner, Andrew R.; Caccese, Jaclyn B.; Chaudhari, Ajit M. W.; Wang, Wei; Lu, Bo; Merfeld, Daniel M. (Frontiers in Neurology, 2025)
IntroductionExternal continuous perturbations using a motion platform have been developed by employing either sum-of-sines (SoS) or a pseudorandom ternary sequence (PRTS) of numbers to quantify body sway evoked in the medial-lateral (ML) or anterior-posterior (AP) directions, which ultimately helps understand the human postural control system. These stimuli have been provided via pitch tilts of the motion platform for evaluations of AP balance responses or roll tilts for ML balance responses. However, little is known about whether a healthy postural control system responds to 2-dimensional (2D) perturbations similarly when the perturbation stimuli are provided in semicircular canal coordinates (i.e., right-anterior/left-posterior (RALP) and left-anterior/right-posterior (LARP)) versus roll/pitch coordinates. Stimuli provided in either set of coordinates were orthogonal in both time and space. Our 2D platform perturbations provided in RALP/LARP coordinates will have the potential to better assess the contribution of each pair of the vertical semicircular canals to postural control for individuals with dysfunction of the vertical semicircular canals.MethodsTo address this knowledge gap, we developed four different balance perturbation trajectories using sum-of-sines (SoS) signals and simultaneously provided those stimuli in (i) roll and pitch, (ii) RALP and LARP, and (iii) roll, pitch, RALP, and LARP dimensions. Center of pressure (CoP) data were collected from 24 healthy participants (40 13 years of age) on a commercially available motion platform (Virtualis Motion VR, Perault, France). A discrete Fourier transform (DFT) was applied to the CoP data to identify responses at perturbed frequencies (i.e., spectral response components).ResultsWe found that ML and AP postural responses were not significantly different when the platform perturbations were simultaneously provided in RALP/LARP coordinates versus roll/pitch coordinates.DiscussionThis finding suggests that our 2D platform perturbations in RALP/LARP coordinates allow us (1) to compare ML and AP responses evoked by RALP and LARP stimuli to existing literature showing those responses evoked by roll and pitch stimuli and (2) to characterize postural responses for individuals with sensory deficits to better isolate contributions of the vertical semicircular canals to postural control.